2000
DOI: 10.1007/pl00008159
|View full text |Cite
|
Sign up to set email alerts
|

Developing prolamine protein bodies are associated with the cortical cytoskeleton in rice endosperm cells

Abstract: The mRNAs that encode the prolamine storage proteins in rice (Oryza sativa L.) endosperm cells are enriched on the surface of the prolamine protein bodies (PBs), a subcellular structure consisting of a prolamine intracisternal granule surrounded by rough endoplasmic reticulum membrane. Previous biochemical studies (D.G. Muench et al., 1998, Plant Physiol. 116: 559-569) have shown that prolamine mRNAs may be anchored to the PB surface via the cytoskeleton. To better understand the mechanism and role of mRNA loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Interestingly, 15 actin-related and 10 tubulin-associated cytoskeletal proteins were also identified in the intact PB proteome (Supplementary Table S3). These data support the hypothesis that the cortical actin filament and microtubule networks are involved in anchoring and maintaining the PB鈥損olyribosome鈥揈R membrane complex to the plasma membrane (Muench et al , 2000). Taken together, our data indicated that ribosomes and ER membranes (probably derived from rough ER), as well as the cytoskeleton, although in the peripheral region, are most likely the integral compartments of zein PBs.…”
Section: Resultssupporting
confidence: 85%
“…Interestingly, 15 actin-related and 10 tubulin-associated cytoskeletal proteins were also identified in the intact PB proteome (Supplementary Table S3). These data support the hypothesis that the cortical actin filament and microtubule networks are involved in anchoring and maintaining the PB鈥損olyribosome鈥揈R membrane complex to the plasma membrane (Muench et al , 2000). Taken together, our data indicated that ribosomes and ER membranes (probably derived from rough ER), as well as the cytoskeleton, although in the peripheral region, are most likely the integral compartments of zein PBs.…”
Section: Resultssupporting
confidence: 85%
“…As shown, they are smaller and less spherical than the rhodamine B-stained vesicles (Figure聽4B, labelled in red), corresponding to prolamine-containing PBs (PB-I). Rhodamine B hexyl ester binds strongly to rice prolamine and it is regularly used for fluorescent labelling of PB-I [34]. The merged images in Figure聽4B clearly show that cecropin A was absent from PB-I, since no colocalization is observed.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of cytoskeleton and, in particular, actin filaments would serve two functions. First, it would serve as the anchoring site for RNAs transported from the nucleus (Singer, 1992;Bogucka-Glotzer and Ephrussi, 1996;Bloom and Beach, 1999;Muench et al, 2000). Indeed, evidence was obtained showing that prolamine RNAs are retained on prolamine PBs by detergent-resistant, The 10-kD zein RNA is located on the PB-ER, indicating that it contains a cis sorting determinant in the coding sequence.…”
Section: Discussionmentioning
confidence: 99%